Desidratação de polpa de manga em leito de espuma com e sem intermitência térmica - Chaux Gutiérrez, Ana María [UNESP] (2015)
Foam mat drying and thermal intermittence were developed with the objective of obtaining good quality food products and of improving the energy efficiency of the process. The objective of this study was to investigate the foam mat drying process parameters, with and without thermal intermittence, and evaluate their effects on the physical and nutritional properties of mango powder. The effects of temperature (60 and 80 ºC), Emustab concentration (2% w/w), Albumin concentration (10% w/w), an Emustab-Albumin mixture and thermal intermittence on the drying kinetics, of the manga pulp foam color maintenance, carotenoid content and retention, and the solubility of the dried product, were studied using a 23 factorial experimental design. Thermal intermittence was applied by reducing the temperature by 20 ºC for a determined period during drying, and subsequently returning to the initial drying temperature. The foams produced presented high effective water diffusion coefficients, allowing for low moisture contents and low water activities to be obtained in short processing times. Thermal intermittence resulted in slightly higher diffusivity values, when determined as the mean coefficients for the whole drying process. The color parameters L* and b* of the mango powder were affected by the type and concentration of the foaming agents, the foams produced using Emustab resulting in lighter colored, yellower powders. The parameters a* and ºHue (h*) were affected by the temperature and by the Emustab and albumin concentrations, Emustab being the most significant factor with respect to the red color (a*) and the value for h*, promoting a decrease in the first and increase in the second, providing a yellowy-orangey hue typical of mango. Expressive carotenoid retention was obtained from the foams produced using albumin and the albumin-Emustab mixture at 80 ºC, with values of 88.9 and 78.5 %, respectively. Thermal...